2018
DOI: 10.1371/journal.pone.0202849
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree data indicate rapid inbreeding and loss of genetic diversity within populations of native, traditional dog breeds of conservation concern

Abstract: Increasing concern is directed towards genetic diversity of domestic animal populations because strong selective breeding can rapidly deplete genetic diversity of socio-economically valuable animals. International conservation policy identifies minimizing genetic erosion of domesticated animals as a key biodiversity target. We used breeding records to assess potential indications of inbreeding and loss of founder allelic diversity in 12 native Swedish dog breeds, traditional to the country, ten of which have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The loss of genetic variability and the increase in inbreeding levels coupled with the consequent reduction in the effective population size in a high number of pedigree canine populations could be considered the main risk factor in conservation project definitions [12,15,[41][42][43][44]. In general, the reported results show low F PED in the studied subjects [44].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The loss of genetic variability and the increase in inbreeding levels coupled with the consequent reduction in the effective population size in a high number of pedigree canine populations could be considered the main risk factor in conservation project definitions [12,15,[41][42][43][44]. In general, the reported results show low F PED in the studied subjects [44].…”
Section: Discussionmentioning
confidence: 76%
“…The loss of genetic variability and the increase in inbreeding levels coupled with the consequent reduction in the effective population size in a high number of pedigree canine populations could be considered the main risk factor in conservation project definitions [12,15,[41][42][43][44]. In general, the reported results show low F PED in the studied subjects [44]. The effectiveness of the molecular dissection of inbreeding is shown by the F ROH (equation 2) results, which reveal the genomic relationship among the studied individuals as demonstrated by different researchers [8,16,45].…”
Section: Discussionmentioning
confidence: 99%
“…This way of reducing the inbreeding is confirmed by studies concerning dog breeding and endangered breeds with small populations [13, 16, 33, 55]. These observations are alarming since reduced genetic variation and inbreeding are generally associated with the loss of the adaptive potential and reduced options of effective selection [10, 52, 56]. We note that this rapid genetic diversity loss is parallel to an increasing requirement of dogs for a number of different purposes in the modern society [8, 57-59].…”
Section: Discussionmentioning
confidence: 80%
“…Breeds like the Swedish lapphund and the Swedish vallhund, however, reach almost as high average F- 0.09 -in spite of pedigree sizes of several thousand individuals, census sizes of well over 1000, and over 50 founders. Similarly, the Swedish elkhound and the Drever have pedigrees comprising over 50,000 dogs, with over 10,000 defined as alive in 2012 but average F is over 0.07 [10]. A study of genealogical parameters for a number of breeds in Australia found that the mean inbreeding coefficient ranged from 0 to 0.101 across 32 analysed breeds [53].…”
Section: Discussionmentioning
confidence: 99%
“…In many ways dogs are an ideal model for the study of genetic erosion and population recovery. Genetic diversity in many common domestic dog breeds has been declining systematically since the beginning of the 1800's, when modern breeding practices came into fashion (Jansson & Laikre, 2018). As such, inbreeding in domestic dog breeds is substantial and widespread (Freedman et al, 2014;Kettunen, Daverdin, Helfjord, & Berg, 2017;Pedersen, Pooch, & Liu, 2016;Sams & Boyko, 2018) and has led to an increase in recessive deleterious mutations of high effect (Jagannathan et al, 2019;Marsden et al, 2016) as well as general inbreeding depression (Chu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%